Linking Religiosity and Work-Family Conflict to Employee Performance via Job Satisfaction: A Structural Equation Modeling Approach - Silitonga, Nelson; Suroso; Gazali; Chidir, Gusli; Asbari, Masduki (IJOSMAS, 2024)
The objective of this study is to investigate the impact of religion and work-family conflict on employee performance by utilizing job satisfaction as an intervening variable. The workforce of the manufacturing industry will be used as the sample population, and there will be a total of 120 individuals involved in the study. For the purpose of this study, the data gathering method that was utilized was a questionnaire. The analysis method that was utilized was Structural Equation Modelling (SEM), and the SmartPLS version 3.0 was utilized. The result of this research showed that religiosity has a significant positive effect on job satisfaction, the work-family conflict has a significant negative effect on job satisfaction, religiosity has a significant positive effect on employee performance, work-family conflict does not significantly affect employee performance, job satisfaction has a significant positive effect to employee performance, religiosity has a significant positive effect to employee performance through job satisfaction as an intervening variable, work-family conflict does not significantly affect the employee performance through job satisfaction as an intervening variable. It is possible that the findings of this study could serve as a foundation for enhancing and sustaining the performance of an organization by focusing on religious improvement and addressing the work-family conflict that is encountered by working individuals.